The Polymorphism of Voltage-Gated Sodium Channel Gene in Culex Mosquitoes in Banyuwangi District, Indonesia - Yasmin Azzahra Arifin; Hanifah Dzakiyah; Catherine Canina Charunita; Sakura Alya Ashari; Winna Putri Veliarta; Muhammad Akbar Panjinegara; Francesca Giovanetti; Carlo Montagna; Wojciech Jankowski; Muhammad Fathoni; Binarri Augustya; Lynda Rossyanti; Suhintam Pusarawati; Basuki, Sukmawati (Andalasian International Journal of Entomology, 2024)
Culex mosquito is able to act as transmission vector of filariasis and Japanese encephalitis. Both diseases occur in Indonesia and filariasis exists in Banyuwangi district. The Voltage-Gated Sodium Channel (VGSC) gene mutations are related to pyrethroid insecticide resistance, especially L1014F/S mutations have not yet been fully studied in Indonesia. This study aimed to investigate the polymorphism of VGSC gene mutation in Culex mosquitoes in Banyuwangi District of East Java Province, Indonesia. Culex mosquitoes were collected using mosquito trap in a two-day collection from Banyuwangi Sub-district and two sub-villages in Cluring Sub-district of Banyuwangi District in August 2023. Culex mosquitoes were identified by morphological examination and Culex DNA was extracted by Chelex100 from each Culex mosquito. The polymorphism of VGSC gene mutations of L1014F/S were determined by Allele Specific-Polymerase Chain Reaction (AS-PCR). A total of 62 Culex mosquitoes were analyzed. The wild type Culex mosquitoes were found predominant (77%, 48/62). Two types of homozygous mutations were identified as 1014F and 1014 S (16%, 10/62 and 2%, 1/62, respectively). The heterozygous mutation was only 1014F/S type with frequency of 5% (3/62). The predominance of wild type Culex mosquitoes indicated that Culex population in the study areas is still susceptible to pyrethroid insecticide. However, the mutant types of Culex are already occurred, so insecticide resistance among Culex mosquitoes is required to be regular monitoring.